Effect and cardiovascular safety of adding rosiglitazone to insulin therapy in type 2 diabetes: A meta‐analysis. Issue 1 (18th June 2014) - Lu, Yu; Ma, Delin; Xu, Weijie; Shao, Shiying; Yu, Xuefeng
Abstract Aims/Introduction Recently, the use of rosiglitazone has been limited or withdrawn from the market as a result of cardiovascular risk. However, theoretically adding rosiglitazone to insulin could help insulin to decrease the glucose level. The present meta‐analysis was designed to investigate the effect and safety of adding rosiglitazone to insulin therapy in type 2 diabetes. Materials and Methods We searched published and unpublished databases through to March 2012. Randomized controlled trials (RCTs) comparing rosiglitazone in combination with insulin (RSG + INS) vs insulin alone (INS) in type 2 diabetes with outcomes including glycated hemoglobin levels, insulin dose, lipid parameters, blood pressure, edema and cardiovascular adverse events were selected. Results Nine RCTs with durations of 24–26 weeks involving 1, 916 patients were included. The RSG + INS group showed significantly decreased glycated hemoglobin levels by 0.89% (P < 0.00001) with an 8.48‐U reduction in daily insulin dose (P <0.00001). However, the risks of hypoglycemia and edema were more frequent in the RSG+INS group (P < 0.0001; P = 0.03, respectively). Total cholesterol level was significantly increased in the RSG+INS group (P < 0.00001), but none of the high‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol, very low‐density lipoprotein cholesterol or triglyceride levels were significantly different between groups. There were no significant differences between groups with regard to the risks of myocardial infarction, heart failure, cardiovascular death or all‐cause death. Conclusions Rosiglitazone could help type 2 diabetes patients with poorly controlled glucose with insulin therapy to decrease glucose levels and reduce their daily insulin dose, but at the cost of increased total cholesterol level, hypoglycemia and edema risk. Compared with insulin therapy, adding rosiglitazone to insulin did not increase the risks of myocardial infarction, heart failure, cardiovascular death or all‐cause death.